2001
DOI: 10.1021/np0005762
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Acridone Alkaloids from Swinglea glutinosa

Abstract: A new prenylated acridone alkaloid, 1,3,5-trihydroxy-2,8-bis(3-methylbut-2-enyl)-10-methyl-9-acridone (1), was isolated from the stembark of Swinglea glutinosa, along with three known acridone alkaloids, 5-hydroxynoracronycine (2), 1,3,5-trihydroxy-4-methoxy-2-(3-methylbut-2-enyl)-10-methyl-9-acridone (3), and 1,3,5-trihydroxy-4-methoxy-10-methylacridone (4). The isolated alkaloids were assessed in vitro against chloroquine-sensitive and -resistant Plasmodium falciparum strains and for cytotoxicity using HeLa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 18 publications
1
20
0
3
Order By: Relevance
“…Assim, a substância 2 foi definida como a N-benzoiltiramina (2), a qual foi isolada anteriormente dos frutos de Limonia acidissima. 2,9 A substância 3 foi isolada como um sólido branco amorfo e nos espectros de RMN 1 Biogeneticamente, a substância 3 pode ser formada a partir da 2 O-prenilada, com posterior formação de epóxido entre C-2'' e C-3'', e abertura deste levando ao diol. A metila da unidade prenila poderia ter sido oxidada a aldeído e, posteriormente, a ácido carboxílico e, em seguida, sofrer uma eliminação descarboxilativa com simultânea eliminação de água (Figura 3).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Assim, a substância 2 foi definida como a N-benzoiltiramina (2), a qual foi isolada anteriormente dos frutos de Limonia acidissima. 2,9 A substância 3 foi isolada como um sólido branco amorfo e nos espectros de RMN 1 Biogeneticamente, a substância 3 pode ser formada a partir da 2 O-prenilada, com posterior formação de epóxido entre C-2'' e C-3'', e abertura deste levando ao diol. A metila da unidade prenila poderia ter sido oxidada a aldeído e, posteriormente, a ácido carboxílico e, em seguida, sofrer uma eliminação descarboxilativa com simultânea eliminação de água (Figura 3).…”
Section: Resultsunclassified
“…1 Como toda planta pertencente à família Rutaceae, é caracterizada por alcaloides acridônicos, cumarinas e amidas. [1][2][3] Segundo o sistema de classificação de Engler (1931) o gênero Swinglea encontra-se classificado na subfamília Aurantioideae, tribo Citreae, subtribo, Balsamocitrinae. 4 Esta subfamília é considerada de caráter natural pelos vários sistemas de classificação, ou seja, sua constituição em tribos, subtribos e gêneros não tem sido questionada.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…[24][25][26][27][28][29] From both chemical and pharmaceutical viewpoints, it would be significant to provide a new synthetic route to these heterocyclic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…8 The family Rutaceae contains many secondary metabolites such as alkaloids, flavonoids, coumarins, limonoids and lignans with a large spectrum of biological activities. 9 Studies showed that acridone alkaloids are compounds with promising activity against P. falciparum, 10,11 and also have antiviral 12 and antiproliferative effects on cancer cell lines. 13,14 The Asian genera Citrus and Swinglea are members of the Rutaceae and are included in the subfamily Aurantioideae.…”
Section: Introductionmentioning
confidence: 99%